Efektivitas Transfer Teknologi Pengolahan Beras Siger Terhadap Peningkatan Produktivitas Usaha Beras Tiwul Tradisional - Beni Hidayat (Inovasi Pembangunan : Jurnal Kelitbangan, 2014)
“Siger” rice is cassava analogue rice adopt tiwul making process but with the appearance (more uniform shape, brighter colors) and the flavor is better. “Siger” rice is basically an instant tiwul that have been modernized. Because processed by the same method, the “siger” rice characterized as a functional food as well as traditional Tiwul. In order to transfer “siger” rice processing technology, has developed a pilot center for processing of “Siger” rice in Margomulyo village, Jati Agung, South Lampung. The study aims 1) to assess the effectiveness of technology transfer” siger” rice to increase productivity of traditional tiwul business 2) to reviewing the composition of the functional components of “Siger” rice result of technology transfer . The results showed that 1) the activities of technology transfer has been able to increase the productivity of the business as reflected in production capacity from 10 kg to 100 kg per week; selling price from Rp 8.000/kg to Rp 10.000/ kg ; profits per week from Rp 20.000 to Rp 350.000 ; expanding the marketing reach form Margomulyo village into South Lampung and Bandar Lampung and 2) “Siger” rice of technology transfer characterized as a functional food that is reflected in the high content of dietary fiber (14.95%) and resistant starch (7.78%) ; and more slowly digested the body because it has a low starch digestibility (17.65%).